TINJAUAN YURIDIS TERHADAP PENGGUNA JALAN YANG MENGAKIBATKAN TERJADINYA KERUSAKAN JALAN - Watimah, Watimah; Borman, M. Syahrul; Handayati, Nur (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study examines the juridical review of legal liability for road users who cause road damage in Indonesia. Using a normative legal research approach, this study analyzes the existing legal framework, specifically Law Number 22 of 2009 on Road Traffic and Transportation (UU LLAJ) and its related regulations. The findings indicate that road damage, often caused by over dimension over loading (ODOL) vehicles, creates a duality of responsibility. On one hand, the government, as the road operator, has a legal obligation to maintain and repair roads and can be subject to criminal sanctions for negligence. On the other hand, road users who cause damage are also liable for criminal penalties and civil compensation. Although the legal framework is robust, law enforcement remains suboptimal due to challenges like overlapping authority, budget constraints, and a lack of inter-agency coordination. Therefore, this study concludes that effective law enforcement requires synergy among institutions, the use of technology, and increased public legal awareness to create a safe and sustainable transportation system